EDUPRENEUR MUDA: TRANSFORMASI IDE MAHASISWA MENJADI PRODUK PENDIDIKAN BERNILAI DENGAN PRODUK LKPD - Nurul Aditya Azizah; Najwatul Istiqomah; Selvia Azzahra Apriliandis; Widiani Kusuma Dewi; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This research is motivated by the phenomenon of the low implementation of entrepreneurial values among education students, despite their great potential to innovate in creating creative and contextual learning products that align with 21st-century learning needs. The study aims to examine and describe the process of transforming students’ creative ideas into valuable educational products through the development of digital- based Student Worksheets (LKPD) as an implementation of the edupreneurship concept in higher education. The research employs a descriptive qualitative approach with data collection techniques consisting of in-depth interviews and observations of student entrepreneurs who develop and market their LKPD through social media platforms. Data analysis was carried out through the stages of data reduction, presentation, and conclusion drawing, validated using the member check technique to ensure data credibility. The findings reveal that the use of digital design technology such as Canva serves as the main tool in developing Student Worksheets (LKPD) due to its ease of use, availability of ready-to-use templates, and minimal design skills required. Additionally, promotional strategies through social media platforms such as TikTok and Facebook significantly contribute to helping students produce educational products that are engaging, efficient, and have economic value. This entrepreneurial activity not only provides financial benefits but also strengthens students’ roles as young edupreneurs who contribute to the development of technology-based learning innovations. The implications of this study emphasize the importance of institutional support in fostering a spirit of creative and sustainable entrepreneurship within academic environments